27+4b=5+6(5b-5)

Simple and best practice solution for 27+4b=5+6(5b-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27+4b=5+6(5b-5) equation:


Simplifying
27 + 4b = 5 + 6(5b + -5)

Reorder the terms:
27 + 4b = 5 + 6(-5 + 5b)
27 + 4b = 5 + (-5 * 6 + 5b * 6)
27 + 4b = 5 + (-30 + 30b)

Combine like terms: 5 + -30 = -25
27 + 4b = -25 + 30b

Solving
27 + 4b = -25 + 30b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-30b' to each side of the equation.
27 + 4b + -30b = -25 + 30b + -30b

Combine like terms: 4b + -30b = -26b
27 + -26b = -25 + 30b + -30b

Combine like terms: 30b + -30b = 0
27 + -26b = -25 + 0
27 + -26b = -25

Add '-27' to each side of the equation.
27 + -27 + -26b = -25 + -27

Combine like terms: 27 + -27 = 0
0 + -26b = -25 + -27
-26b = -25 + -27

Combine like terms: -25 + -27 = -52
-26b = -52

Divide each side by '-26'.
b = 2

Simplifying
b = 2

See similar equations:

| 27+4b=5+6(5b-5)answer | | 3.14d=298.2 | | -10n-15=-6n+17 | | 3x^2+12x+40=0 | | (x^2-4x)(x^2+4x)=x^2-4x+20 | | -3y=-9-6x | | 4(-5h-2)=-68 | | -3x+4x-3=5 | | a(x-b)-b(x+a)=0 | | (m-1)x^2-2x+1-m=0 | | 36=x-3 | | -21+6(x+3)=33 | | C^2+7c-18= | | (5-15y)-(12+16y)= | | -5u+41=6(u+5) | | 9=9x-124 | | (x-3)*(x^2-6x)=7 | | wy+5y=T | | 4x+16w+64= | | x+4x=33045 | | X^2+5*x+34=0 | | 6x-4x=6x-8x+2 | | -4-6(6m-2)=-64 | | 2.39=m(3.29)+0.59 | | -2x-8x=4-8x | | 5x-(8-x)=4a-10 | | 5p-2p=54 | | 1.3x-4.42=x-2.5 | | 4w+2w=48 | | (-1.59)(-0.5)= | | 240=lwh | | 0.50x+0.45(30)=47.5 |

Equations solver categories